2020
DOI: 10.1002/cpt.1748
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Maternal and Fetal Dolutegravir Exposure by Integrating Ex Vivo Placental Perfusion Data and Physiologically‐Based Pharmacokinetic Modeling

Abstract: Antiretroviral therapy during pregnancy reduces the risk of vertical HIV-1 transmission. However, drug dosing is challenging as pharmacokinetics (PK) may be altered during pregnancy. We combined a pregnancy physiologicallybased pharmacokinetic (PBPK) modeling approach with data on placental drug transfer to simulate maternal and fetal exposure to dolutegravir (DTG). First, a PBPK model for DTG exposure in healthy volunteers was established based on physiological and DTG PK data. Next, the model was extended wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 46 publications
3
32
1
Order By: Relevance
“…Furthermore, the maternal dolutegravir PK parameters during pregnancy predicted by the model employed in this present study were similar to those predicted by Liu et al ( 72 ). Additionally, the predicted fetal exposure to dolutegravir in the present study was comparable to that reported by Freriksen et al ( 71 ). Although, fetal-to-maternal AUC plasma exposure ratio was predicted in our study, it was assumed to be similar to and within the range of the cord blood-to-maternal blood concentration ratios predicted in their study and observed clinical data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the maternal dolutegravir PK parameters during pregnancy predicted by the model employed in this present study were similar to those predicted by Liu et al ( 72 ). Additionally, the predicted fetal exposure to dolutegravir in the present study was comparable to that reported by Freriksen et al ( 71 ). Although, fetal-to-maternal AUC plasma exposure ratio was predicted in our study, it was assumed to be similar to and within the range of the cord blood-to-maternal blood concentration ratios predicted in their study and observed clinical data.…”
Section: Discussionsupporting
confidence: 91%
“…Although, fetal-to-maternal AUC plasma exposure ratio was predicted in our study, it was assumed to be similar to and within the range of the cord blood-to-maternal blood concentration ratios predicted in their study and observed clinical data. Likewise, the C max and the C min of the maternal plasma concentration predicted by our model was lower and higher, respectively, in comparison to their reported values ( 71 ). Further studies are still suggested to establish this assumption of similarity.…”
Section: Discussioncontrasting
confidence: 78%
“…Maternal and umbilical cord PK prediction [119] Efavirenz (CYP2B6) Similar PK during 2 nd and 3 rd trimesters to those observed in non-pregnant women [120][121][122].…”
Section: Discussionsupporting
confidence: 52%
“…PBPK to Predict Fetal Exposure of Drugs PBPK has been used to predict fetal exposure of drugs, and examples are discussed below and in Table 4. Freriksen et al 63 developed a PBPK model to predict fetal exposure of dolutegravir by integrating transplacental kinetics obtained from ex vivo dual-side cotyledon perfusion experiments. The simulated fetal exposure after maternal dosing in third trimester was in accordance with the observed clinical cord blood data.…”
Section: Application Of Pbpk Modeling To Predict Exposure Of Renally mentioning
confidence: 99%